Hereditary angioedema: health-related quality of life in Canadian patients as measured by the SF-36. Issue 1 (December 2017) - Jindal, Nina; Harniman, Elaine; Prior, Nieves; Perez-Fernandez, Elia; Caballero, Teresa; Betschel, Stephen
Abstract Background Hereditary angioedema (HAE) is a rare but serious condition characterized by recurrent spontaneous attacks of angioedema affecting superficial tissues of upper respiratory and gastrointestinal tracts. The potentially fatal and disfiguring nature of HAE impacts the health-related quality of life (HRQoL) of patients with this condition. Objectives To assess the health-related quality of life of Canadian patients with HAE using the 36-item Short-Form Health Survey (SF-36v2). Methods Twenty-one patients living in Canada over age 18 with known diagnosis of hereditary angioedema due to C1-INH deficiency (HAE), completed the SF-36v2 (generic HRQoL questionnaire). Results were compared to Canadian normative data by converting the SF-36 scores into z scores. Results The SF-36v2 showed a significant reduction in general health (p = 0.0063) in patients with HAE when compared with healthy Canadians. Percentage of patients with z scores below 0.8 (large effect) was 47.6% for general health subscale, 33.3% for bodily pain and vitality subscales and 28.6% for physical component scores. Mean scores of eight dimensions ranged from 57.7 to 88.9. Mean Physical and mental component scores were 49.1 and 50.4. Internal consistency of evaluation was demonstrated by Cronbach's alpha value above 0.7 for all scales. General perception of health was significantly different in these patients, compared to Canadian normative data. Conclusions This study of Canadian patients with HAE shows that General Health is most frequently affected followed by Bodily Pain and Vitality, as measured by SF-36v2. The SF-36v2 offers valuable insight to assess quality of life in patients with HAE, however a larger number of Canadian patients and specific tools for assessment are needed for better evaluation.